Perancangan Alat Pemantauan Berkelanjutan Kualitas Udara Dalam Ruangan - Sholahudin, Sholahudin; Yudono, Muchtar Ali Setyo; Suryana, Anang (Komputika : Jurnal Sistem Komputer, 2024)
Indoor air pollution is a significant threat because most human activities take place indoors. Several previous studies have proposed indoor air quality monitoring systems. Based on the literature reviewed, an opportunity identified from previous research is the change in the selection of the PM2.5monitoring sensor from GP2Y1010AUF, which is not specifically designed for PM2.5, to the ZH03B sensor, which is specifically designed for PM2.5measurement. The intersection of three air quality regulations (two national and one international) results in the measurement of four pollutants: PM2.5 (particulate matter 2.5), PM10 (particulate matter 10), NO2 (nitrogen dioxide), and CO (carbon monoxide). The system design is based on a literature review of the components, calculations, and hardware and software required. Detection data is stored on a memory card and Google Sheets, allowing users to view data history through a website published by Google Sheets. Additionally, the detection device's accuracy compared to other detectors is 93.55% for PM2.5, 93.13% for PM10, 97.10% for NO2, and 96.60% for CO.